2016
DOI: 10.1371/journal.pone.0156689
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Radiosensitivity and Cellular Characterization of 27 Canine Cancer Cell Lines

Abstract: Canine cancer cell lines have progressively been developed, but are still underused resources for radiation biology research. Measurement of the cellular intrinsic radiosensitivity is important because understanding the difference may provide a framework for further elucidating profiles for prediction of radiation therapy response. Our studies have focused on characterizing diverse canine cancer cell lines in vitro and understanding parameters that might contribute to intrinsic radiosensitivity. First, intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…This study is the first report of next-generation sequence analyses across this panel of 33 canine cancer cell lines. These cell lines have been previously used for preclinical screening of therapeutics to assess their potential for use in the treatment of spontaneous canine cancer (10,30,31). We found that the mutational burden of these cell lines varied from 15.79 to 129.37 mutations per MB.…”
Section: Discussionmentioning
confidence: 92%
“…This study is the first report of next-generation sequence analyses across this panel of 33 canine cancer cell lines. These cell lines have been previously used for preclinical screening of therapeutics to assess their potential for use in the treatment of spontaneous canine cancer (10,30,31). We found that the mutational burden of these cell lines varied from 15.79 to 129.37 mutations per MB.…”
Section: Discussionmentioning
confidence: 92%
“…Immediately after irradiation, cells were trypsinized and replated. The first post irradiation metaphase cells were harvested with 0.1 μg/mL Colcemid (Invitrogen Life Technologies) treatment and prepared as a standard method [ 57 ]. Samples were treated in 75 mM KCl solution for 20 min at 37 °C and fixed in 3:1 (methanol: acetic acid) Carnoy fixation solution three times.…”
Section: Methodsmentioning
confidence: 99%
“…Combination of doxorubicin, cisplatin vinblastine or cyclophosphamide with radiotherapy of tonsillar squamous carcinoma of dog yielded a favourable higher rate of therapeutic response and signi cantly longer survival times [54]. But radiotherapy is a viable alternative for the palliative treatment of canine oral melanoma [43], in spite of the fact that hypoxia has negative in uence on determining response to conventional therapy [56], suggesting that substantial differences in intrinsic radio-sensitivity exist in canine cancers [57]. Fluorodeoxyglucose (FDG)/PET is an effective imaging technique for lymph mode staging of locally advanced cervical carcinoma with negative computed tomography (CT) ndings, despite PET-CT could customize and guide brachytherapy planning [58].…”
Section: Discussionmentioning
confidence: 99%